When security and medicine missions conflict: confidentiality in prison settings. Issue 2 (13th June 2016) - Allen, Scott A.; Aburabi, Raed
Abstract : Purpose: – It is a simple fact that prisons cannot exist – practically, legally, ethically or morally – without the support of physicians and other health professionals. Access to adequate healthcare is one of the fundamental measures of the legitimacy of a jail or prison. At the same time, there is a fundamental tension in the missions of the prison and doctor. The primary mission of the prison is security and often punishment. Reform and rehabilitation have intermittently been stated goals of prisons in the last century, but in practice those humane goals have rarely governed prison administrative culture. The primary mission of the physician is to promote the health and welfare of his or her patient. The paper aims to discuss these issues. Design/methodology/approach: – At times, what is required to serve the patient's best interest is at odds with the interests of security. Much of the work of the prison physician does not conflict with the operation of security. Indeed, much of the work of the prison physician is allowed to proceed without much interference from the security regime. But given the fundamental discord in the legitimate missions of security vs medicine, conflict between the doctor and the warden is inevitable. Findings: – In this paper, the authors consider the example of patient confidentiality to illustrate this conflict, using case examples inspired by real cases from the experience of the authors. Originality/value: – The authors provide an ethical and practical framework for health professionals to employ when confronting these inevitable conflicts in correctional settings.